2002
DOI: 10.3354/meps233283
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic habitats of two sympatric North Pacific albatrosses during the breeding season

Abstract: We characterized the movements and oceanographic habitats of black-footed (Phoebastria nigripes) and Laysan (P. immutabilis) albatrosses during the brooding and the rearing periods of the breeding cycle. Analyses of satellite telemetry data in conjunction with remotely sensed sea surface temperature and chlorophyll concentrations revealed substantial differences in habitat use between these 2 sympatrically breeding species. During the brooding period, black-footed albatross restricted their foraging to tropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
202
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(219 citation statements)
references
References 63 publications
11
202
2
4
Order By: Relevance
“…Therefore, we sampled a single central breast contour feather from all remaining individuals. Because black-footed albatrosses range widely throughout the Pacific Ocean while foraging within a lifetime (39,46,47), we did not expect differences in collection locality to confound signals of temporal variation in bioavailable Hg exposure. We similarly sampled central breast feathers for Hg analysis from russet-crowned motmots and Altamira orioles.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we sampled a single central breast contour feather from all remaining individuals. Because black-footed albatrosses range widely throughout the Pacific Ocean while foraging within a lifetime (39,46,47), we did not expect differences in collection locality to confound signals of temporal variation in bioavailable Hg exposure. We similarly sampled central breast feathers for Hg analysis from russet-crowned motmots and Altamira orioles.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern is not surprising given that shelf regions are usually more productive than adjacent regions of deep ocean. Among the species foraging over the basin are albatrosses, which export energy to islands to the southwest of the study area (Hyrenbach et al, 2002), and stormpetrels that may export small amounts of energy to the coastal zone where they nest. Hunt et al (2000) ARTICLE IN PRESS found that the Gulf of Alaska PICES region had the highest densities of seabirds in any of the PICES regions for which data were available.…”
Section: Article In Pressmentioning
confidence: 99%
“…Detection of such macrohabitat selection is not straightforward, however, as overall foraging ranges of males and females may overlap considerably, and even if there are apparent differences in core areas (e.g. Hyrenbach et al 2002), these could conceivably result from a combination of individual preferences unrelated to gender, given the small sample sizes.…”
Section: Introductionmentioning
confidence: 99%